2015
DOI: 10.1016/j.jconrel.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules targeting microRNA for cancer therapy: Promises and obstacles

Abstract: Aberrant expression of miRNAs is critically implicated in cancer initiation and progression. Therapeutic approaches focused on regulating miRNAs are therefore a promising approach for treating cancer. Antisense oligonucleotides, miRNA sponges, and CRISPR/Cas9 genome editing systems are being investigated as tools for regulating miRNAs. Despite the accruing insights in the use of these tools, delivery concerns have mitigated clinical application of such systems. In contrast, little attention has been given to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 154 publications
0
72
0
Order By: Relevance
“…However, the mechanisms underlying the anticancer activities are yet to be elucidated. Studies are currently focussing on the identification and development of small molecules that inhibit major cell signalling pathways, as an important strategy in anticancer drug research (51)(52)(53). The present study investigated the effects of cucurbitacin B on cell proliferation and the MAPK and JAK2/STAT3 pathways in U-2 OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying the anticancer activities are yet to be elucidated. Studies are currently focussing on the identification and development of small molecules that inhibit major cell signalling pathways, as an important strategy in anticancer drug research (51)(52)(53). The present study investigated the effects of cucurbitacin B on cell proliferation and the MAPK and JAK2/STAT3 pathways in U-2 OS cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrantly expressed miRNAs contribute to many biological processes including tumor initiation and progression, apoptosis, and maintenance of CSCs and EMT phenotype [9-11]. Studies including ours have shown the importance of miRNAs and CSCs in cancer progression and metastasis, making their significance as biomarkers and potential targets for reversing drug resistance [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that miRNAs are involved in regulating several cellular functions, including cell proliferation, apoptosis, motility and differentiation (5,6). Abnormal expression and function of miRNAs has been confirmed to serve important roles in different types of human cancers, including GC (7,8). Multiple miRNAs are regarded as attractive biomarkers and potential therapeutic targets for GC (9,10).…”
Section: Introductionmentioning
confidence: 99%